Sheoak recorded by Peapod Productions in the Central Australian Folk Society collection. - Alice Springs Folk Club.; Central Australian Folk Society (1980)
Folkloric recording
The three ravens -- A miner's lullaby -- The two magicians -- Convict maid -- Foolish, incredibly foolish -- Adieu sweet lovely Nancy -- Sally free and easy -- Crafty maids policy -- Buttermilk Hill -- Mary and the soldier -- My Johnny was a shoemaker -- Sailor home from the sea -- Of all the birds that I ever see -- My husband's got no courage in him -- Lady Margaret and sweet William -- Three drunken maidens -- On the banks of the Condamine -- A miner's lullaby -- The two magicians.
Recorded December 1980.
Digital master available
Donated by Liz Bongers CAFS.
Summary not yet available.
Keywords: Folk songs, English -- Australia; Folk music -- Australia